A Facet Theory Model for Integrating Contextual and Personal Experiences of International Students - Hackett, Paul M. W. (Journal of International Students, 2014)
The purpose of this article is to use a facet theory research approach to provide a clear, coherent, and integrated model of international students’ experiences based upon the findings of psychological research into students when studying abroad. In research that employs a facet theory approach events are classified in terms of their constituent parts or facets and the sub-elements of facets. The specification of facets serves to allow accumulative knowledge and theory construction. A model is proposed in the form of a mapping sentence with three background facets and four content facets. How the mapping sentence forms a flexible template for designing, conducting and analyzing research into international students’ experiences is discussed, as is the potential in using facet theory to develop a cumulative body of knowledge about this student group.